Apatite fission-track (AFT) single-grain data (Table S4) - Falkowski, Sarah; Ehlers, Todd A (In: Falkowski, S; Ehlers, TA (2023): Low-temperature thermochronometric data (AHe, AFT, ZHe, ZFT) from three bedrock sample transects across the eastern Central Andes, southern Peru [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955437, 2023)
This dataset contains 447 single-grain data for 24 samples acquired for apatite fission-track (AFT) dating. AFT data were acquired between 2020 and 2021 using the external detector and zeta-calibration techniques at the University of Tübingen, Germany.
Keywords: apatite fission-track thermochronology; Apatite (U-Th)/He thermochronology; Central Andes; erosion; exhumation; low-temperature thermochronology; South Peru; zircon fission-track thermochronology; zircon (U-Th)/He thermochronology